A Narrative Analysis of the Political Economy Shaping Policy on Child Undernutrition in India. Issue 2 (March 2017) - Nisbett, Nicholas
ABSTRACT: This article examines two narratives on the subject of child undernutrition in India espoused by competing sides of the policy elite. It argues that undertaking narrative policy analysis in a structured fashion helps to elucidate a clearer sense of the underlying positions within this important area of development discourse. India's high rates of child undernutrition have become a battleground of positions on the country's growth trajectory, revealing of the wider assumptions, ideologies and manifestations of power of the various actors espousing particular positions. Recent debates have brought into focus not only the contestation of various causalities and remedies, but also the politics of measurement, data and their interpretation. The results of this analysis are relevant elsewhere in their illumination of the politically public nature of technocratic debates on nutrition and the way in which this public discourse extends beyond the immediate topic to wider ideological divisions and assumptions on growth, equity and recent history.